Implementation of Learning Media Used by Students in Rural Areas: A Mixed-Method Study - Ojat Darojat; Ajat Sudrajat; Darsiharjo Darsiharjo; Lisa Dwi Ningtyas; Cecep Kustandi (Journal of Innovation in Educational and Cultural Research, 2025)
Indonesia is a developing country that cannot be separated from areas far behind regarding access to technology. Thus, community-based education is important to accommodate the lack of access to technology. This research aims to analyze the distance learning model that Universitas Terbuka has implemented to improve students' learning outcomes. This research uses mixed methods. This research involved 75 Universitas Terbuka students. The results of this study provide an overview related to the learning model used and the influence of the learning model on student learning outcomes. In addition, the results of this study show that students who take online classes and use flipped classroom learning media have higher t-test scores than students who take online classes and YouTube video learning media. This study concludes that community-based education is not only limited to empowerment but also advancing the quality of learning through technology-based innovation.